Wavelength Extraction and Analysis of Wind Streaks in SAR Imagery - Lizhang Zhou; Gang Zheng; Chen Wang; Jinliang Shao; Peng Chen; Lin Ren; Xuanwei Wan; Yuanyuan Zhu; He Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
Wind streaks are common and important phenomenon in marine atmospheric boundary layer (MABL), presenting as a weak spatial-quasiperiodic signal in synthetic aperture radar (SAR) imagery. The literature on wind streaks in SAR imagery always focuses on sea surface wind retrieval rather than the relationship between wind streak wavelength and MABL. The objective investigation of the relationship requires automatic and precise wavelength extraction. However, it is a challenging task as the wind streaks are weak signals submerged in intense speckle noise on SAR images, and other phenomena (e.g., waves) can interfere with the extraction at the same time. We proposed an automatic method for extracting wind streak wavelength in SAR imagery. The method comprises a power spectrum density-based extraction algorithm and a subsequent quality control procedure. The algorithm extracts the wind streak wavelength from the one-dimensional power spectrum across the streak direction. This approach differs from conventional methods that rely on the noisy two-dimensional power spectrum of SAR images. The quality control procedure is to eliminate the interference from waves further. We extracted the wind streak wavelengths in 4445 SAR images using the method. Then, we systematically analyzed the wavelength trends regarding the MABL environment parameters and checked the trends using the Mann–Kendall significant test. The results show that the wavelength increases as the parameters (sea surface temperature, sea surface air temperature, air humidity, boundary layer height, and vertical derivatives of temperature and humidity) increase. This finding indicates that thermodynamic instability could be significant in the occurrence of wind streaks.